A REALITY OF MINANGKABAU LANGUAGE AND LITERATURE AND ITS TRANSFORMATION TO A CREATION OF PERFORMANCE WORKS. - Maryelliwati Maryelliwati, S.Sn, M.Pd; Wahyudi Rahmat; Edwar Kemal (Jurnal Gramatika, 2018)
Minangkabau people's literary works are many in both oral, handwritten and printed in various printers. This article will illustrate Minangkabau's Minangkabau form of language into Minangkabau literature and its transition into a showpiece. The forms of writing are manifest in literature. The scope of Minangkabau literature is of course a literary work within the Minangkabau region. Minangkabau literature is an indigenous literature, which is a description of feelings, values and thoughts in the level of the proper path that is expressed in Minangkabau language inherited by oral or kato-kato or rundiang kato bamisa (eg word-like bracket) of a generation of kegenarasi. Therefore, the research of this library is deemed necessary to describe the existence of its form to be sustainable in accordance with the times.